A Homeostatic Model Assessment of Insulin Resistance (HOMA-IR) Relates to Gestational Diabetes, Glycemic Control [1K]. Issue 1 (May 2017) - VanWinden, Kristi; Montoro, Martin; Korst, Lisa M.; Ouzounian, Joseph G.
Abstract : INTRODUCTION: Current methods of evaluating glycemic control in gestational diabetes (GDM) are difficult to standardize within research protocols. The study objective was to validate the use of the HOMA-IR assessment in pregnancies with and without GDM as an indicator of the degree of insulin resistance and as a potential tool for evaluating the response to interventions for GDM aimed at improving insulin sensitivity. METHODS: Prospective cohort study investigating the utility of the HOMA-IR for measuring insulin resistance, beta-cell function, and GDM severity in pregnant women. Each patient had glucose and insulin levels drawn after a minimum 8 hour fast. These values were used to calculate HOMA-IR using published computer models. Measurements were taken between 28 and 34 weeks of gestation in women with diet-controlled gestational diabetes and non-GDM controls, matched for maternal age, gestational age, and body mass index. RESULTS: HOMA-IR levels were calculated prospectively in 134 women with diet-controlled gestational diabetes and 23 controls without GDM. HOMA-IR was significantly greater in the GDM group compared with non-GDM controls (mean 2.53+1.01 versus 2.02+0.90, p=0.0216) and in women with GDM who ultimately required medical therapy for glucose control compared with those who remained diet-controlled (1.42+0.952 versus 2.95+2.680, p < 0.0001). CONCLUSION: HOMA-IR is a simplified measure of insulin resistance and may predict both which pregnant women are at risk for GDM and which patients with GDM are most likely to require medical therapy. HOMA-IR is a potentially valuable tool in studies of interventions for GDM requiring a marker of insulin resistance.